Pengajaran Bahasa Arab untuk Tujuan Pariwisata di Politeknik Pariwisata NHI Bandung - Batmang, Batmang; Akla, Akla; Hasfikin, Hasfikin; Bahdia, Nur (Institut Agama Islam Negeri (IAIN) Metro, 2023)
This research's primary concern and purpose is how Arabic language teaching is used for tourism purposes at the NHI Bandung Tourism Polytechnic (Poltekpar). The research method used in the study is descriptive, using a dialogical qualitative interview design. The results showed that the content of Arabic language materials taught had been adjusted to the scope of work of each division or type of work in hospitality. With two main themes: 1) general Arabic for beginners, which includes introductions, recognizing guests, being at home, when do we go, what day is it today, going to work, what to do on vacation, where is the bank, when to call, what is your favorite color, what is the weather, it is time to travel and go to the doctor 2) Arabic for tourism covers travel plans, overseas travel, at the airport (arrival), calling a taxi, booking a hotel, going to the hotel, registering (hotel), room facilities, breakfast time, resolving complaints, visiting destinations, shopping, leaving the hotel, emergencies and dropping off guests at the airport.